SKRINING IN SILICO POTENSI SENYAWA ALLICIN DARI ALLIUM SATIVUM SEBAGAI ANTIPLASMODIUM - Fatmawaty Fatmawaty; Muhammad Hanafi; Rosmalena Rosmalena; Vivitri Dewi Prasasty (Research Center for Chemistry - LIPI, 2015)
Allicin compound (2-propene-1- sulphinothioat acid S-2-propenyl ester) is known to have potential as antiplasmodium in vitro. However, the inhibitory activity mechanism of Allicin to plasmodium is still unknown. In this research, we determined the inhibitory activity of Allicin in silico. Identification of physicochemical properties of Allicin compound and two Allicin derivatives, Alc1, Alc2 and Ac2Alc3 were also conducted.. Furthermore, analysis of drug-likeness and adsorption-distribution-metabolism-excretion (ADME) were carried out on the Allicin compound and its derivatives to find the potential of these compounds as drug candidates. In determining the specific interaction, we utilized molecular docking analysis between Allicin and its derivatives against a protein target Cysteine Protease (SP). MolecularÂ docking results showed that Allicin derivative, Alc2 (S-prop-2-en-1-yl 3-methylbut-2-ene-1-sulfinothioate, C10H18OS2) has better potential as inhibitors than Allicin, based on the lower bond energies and the inhibition constants, thus Alc2 can be used as an antiplasmodium agent candidate.Keywords: Allicin, Allicin derivatives, drug likeness, ADME, molecular docking